Pengaruh Perbedaan Jenis Kelamin Terhadap Simtom Depresi Pasien Skizofrenia Di Rumah Sakit Jiwa Prof.Dr.M.Ildrem Kota Medan Sumatera Utara Pada Tahun 2017 - Siti Andira; Nanda Sari Nuralita (Buletin Farmatera, 2018)
Abstract: Depressive symptoms in schizophrenia are important not only because they contribute significantly to the suffering caused by the illness, whether positive psychotic symptoms are active or quiscent, but also because they exacerbate deficits in psychosocial functioning and commonly precede attempted and completed suicide. Depressiv symptoms in man often shows itself very differently from female depression, this means that they feel the same difficult emotion but their expression of them is notably different. Depression symptom in woman often express feeling of sadness and hopelessness, depression symptom in male often complain about the physical symptoms of depression, mask their depression with alkoholism or subtance abuce. This study was observational with cross sectional. Population in this study from outpatients in September-October 2017 in Psychiatric hospital Prof.Dr.M.Ildrem Medan, North Sumatera. The sample of the study consisted 113 patients which filtrated from inclusion and exclusion criteria, measuring depression symptom with Beck Depression Inventory II (BDI II), data analyzed with person correlation using Mann-Whitney Test. The result was there has significant differences depression symptom between male (64,19) and female (40,97) patients schizophrenia. Depression symptoms in male schizoprenia patients is more serious p:0,01 (P:<0,05). The conclusion was there has significant differrences depression symptom between male and female patients schizophrenia.Keywords: Depression Symptom, Schizophrenia